ATIM-17. A PHASE I TRIAL OF HYPOFRACTIONATED STEREOTACTIC IRRADIATION (HFSRT) COMBINED WITH NIVOLUMAB (NIVO), IPILIMUMAB (IPI) AND BEVACIZUMAB (BEV) IN PATIENTS (PTS) WITH RECURRENT HIGH GRADE GLIOMAS. (11th November 2019) - Sahebjam, Solmaz; Forsyth, Peter; Tran, Nam; Etame, Arnold; Arrington, John; Jaglal, Michael; Mokhtari, Sepideh; MacAulay, Robert; Wicklund, Melissa; Evernden, Brittany; Gatewood, Tyra; Robinson, Timothy; et al.
Abstract: BACKGROUND: There is strong pre-clinical evidence that combining CTLA4 and PD-1/PDL-1 blockade with antiangiogenic agents and HFSRT independently enhance anti-tumor immune responses and tumor regression. METHODS: This phase I study includes a safety cohort of 6 pts followed by dose expansion cohort of 26 pts. Pts with Bev naïve recurrent WHO grade III or IV gliomas (maximum diameter of enhancing brain lesion ≤ 4 cm) are eligible. An interval of at least 6 months after the end of prior RT is required unless there is a new recurrence outside of the previous RT treatment field. Eligible pts are treated with HFSRT to the recurrent tumor (30 Gy in 5 fractions) and 4 cycles of Nivo (3 mg/kg), Ipi (1 mg/kg) and Bev (15 mg/kg) every 3 weeks followed by Nivo 240 mg and Bev 10 mg/kg every 2 weeks for 4 months. After 4 months, Nivo is administered every 4 weeks at 480 mg flat dose and Bev is continued at every 2 week schedule. The primary study objectives are to determine safety and tolerability of above treatment. Secondary endpoints include response rate, 6 and 9-months survival rates, and exploring tissue and imaging biomarkers. RESULTS: As of June 2019, safety cohort has been completed and accrual to dose expansion cohort is ongoing. Combination of HFSRT, Nivo, Ipi and Bev as above is well tolerated. The most common toxicities were grade 1 anorexia, grade 1 diarrhea, grade 1 elevation of alanine aminotransferase, grade 1 elevation of lipase and grade 1 infusion related reaction. One patient had grade 3 confusion which was reversible with use of corticosteroids. No dose limiting toxicity has been observed. CONCLUSIONS: Combination of HFSRT with Nivo, Ipi and Bev was considered safe to be studied in expansion cohort. Updated safety and efficacy data will be presented.